Effect of connector design on the stress distribution of a cantilever fixed partial denture - Andre R Correia; Joao C. Sampaio Fernandes; Jose C. Reis Campos; Mario A Vaz; Nuno V Ramos; Joao P Martins da Silva (Wolters Kluwer Medknow Publications, 2009)
Context: The design of a fixed partial denture (FPD) is very important to reduce the stresses generated over the supporting tissues. The connector area needs specific conditions due to biological and esthetic demands, and must be well assessed especially in the posterior regions. Aims: To make a stress analysis of a titanium cantilever fixed partial denture executed with the CAD-CAM system Everest®Kavo, in order to optimize the design of the structure, considering the shape and connector's area. Materials and Methods: A finite element analysis mesh was constructed after post-processing the CAD-CAM design. This mesh was submitted to 500 N load to assess the stress distribution within the cantilever (molar) connector. To optimize the design of this connector, a simplified model was created and a stress analysis was done with the software Solidworks®, by modifying the connector's shape and the load. Results: The stress values obtained were of 1.8 GPa, 6.5 times higher than titanium yield tensile strength. The stress analysis in the simplified model revealed lower stresses with an elliptical connector (994 MPa), or a 1 mm fillet (812 MPa). Lower loads suggested lower stresses of 540 MPa (125 N load) and 174 MPa (50 N load). Conclusions: Cantilever titanium connectors with 5.28 mm2 area are insufficient to withstand 500 N loads in a molar size cantilever, but may support normal physiologic loads of 50 N. The connectors should be more elliptical than circular to better withstand vertical loads, and the CAD software should permit the design of fillets in the connector/abutment surface. Future studies should evaluate the size of this fillet.